Vaginal Progesterone as Maintenance Treatment After an Episode of Preterm Labour (PROMISE) Study: A Multicentre, Double-blind, Randomised, Placebo-Controlled Trial. Issue 3 (March 2017) - Palacio, Montse; Cobo, Teresa; Antolín, Eugenia; Ramirez, M.; Cabrera, Francisco; Mozo de Rosales, Francisco; Bartha, José Luis; Juan, Miquel; Martí, Anna; Oros, Daniel; Rodríguez, A.; Scazzocchio, E.; et al.
Abstract : (Abstracted from BJOG 2016;123:1990–1999) A large proportion of both short-term neonatal morbidity and mortality and long-term disability is associated with preterm birth. Women with previous preterm delivery, a short cervical length at midgestation, a twin pregnancy, and an episode of preterm labor arrested with tocolytic medication all have an increased risk of preterm delivery.